MENINGKATKAN KEMAMPUAN GURU MENERAPKAN MODEL PEMBELAJARAN JIGSAW MELALUI SUPERVISI AKADEMIK DI SMP 2 SIBOLANGIT - Achmad Baktiar (JGK (Jurnal Guru Kita), 2022)
Research objectives :(1). To increase the effectiveness of the role of school supervisors in carrying out academic supervision in applying the Jigsaw learning model. (2). To improve the ability of teachers to apply the Jigsaw learning model. Benefits of Research: (1). To increase teacher professionalism. (2). To increase the professionalism of school supervisors to carry out academic supervision of teachers. (3). To motivate teachers to improve their abilities. The research was conducted based on the School Action Model which was carried out through two cycles with the following procedures: (1). Planning; (2). Acting / action; (3). Observing/ Observing; (4). Reflecting/ Reflection; Data analysis was carried out using a descriptive model. Aspects of action weaknesses in each cycle will be reflected as material for improvement in the next cycle. After the action research was carried out, the results obtained were that academic supervision was able to improve the teacher's ability to apply the Jigsaw learning model from Cycle I to Cycle II seen based on the components of the results of observations between cycles. Therefore it is suggested: (1). academic program with follow-up coaching through School Action Research to teachers at school. in order to provide motivation and allocate a budget for teacher Action Research through academic supervision.